Trust-supply chain performance relationships: unraveling the mediating role of transaction cost attributes in agribusiness SMEs - Owot, Godfrey Moses; Okello, Daniel Micheal; Olido, Kenneth; Odongo, Walter (Frontiers in Sustainable Food Systems, 2023)
The mediation effect of transaction cost attributes on the trust-supply chain performance relationships has remained largely under-explored. Particularly, little is known about the mediating role of information sharing, uncertainty and transaction frequency on the trust-supply chain performance relationships in the agri-food sector. Based on the transaction cost theory, this study used logistic regression to investigate the mediating role of transaction cost attributes on the trust-supply chain performance relationships. Data were collected from 396 agribusiness small and medium-sized enterprises, i.e., farmers (n = 203) and traders (n = 193) in Northern Uganda. Analysis was performed using logistic regression in SPSS version 23 and Amos version 23. The results show that, while trust positively influences supply chain performance, information sharing is the only transaction cost attribute that mediates the relationship between trust and supply chain performance. Agribusiness managers, therefore, need to not only renew the effort of sharing accurate and timely information regarding the market's demand for specific volumes and quality of agricultural products and market trends and storage facilities but also utilize the information to become competitive and improve supply chain performance.